Welfare of buffalo heifers in relation to feeding and space allowance - Grasso, F. (Naples Univ., Portici (Italy). Dipartimento di Scienze Zootecniche ed Ispezione degli Alimenti); Rosa, G. De (Naples Univ., Portici (Italy). Dipartimento di Scienze Zootecniche ed Ispezione degli Alimenti); Migliori, G. (Naples Univ., Portici (Italy). Dipartimento di Scienze Zootecniche ed Ispezione degli Alimenti); Bordi, A. (Naples Univ., Portici (Italy). Dipartimento di Scienze Zootecniche ed Ispezione degli Alimenti); Marsico, I. (Basilicata Univ., Potenza (Italy). Dipartimento di Scienze delle Produzioni Animali); Napolitano, F. (Basilicata Univ., Potenza (Italy). Dipartimento di Scienze delle Produzioni Animali) (Italian journal of animal science, 2003)
[The research was carried out on 40 buffalo heifers of approximately 19 months of age; 20 of them had a space allowance of 2.3 indoor slatted floor + 15 outdoor yard square m/head, while only 2.3 square m/head were assigned to the other 20. Within each treatment, 2 dietary protein levels were adopted: high (10 subjects) and low (10 subjects). To monitor the stress, the following aspects were evaluated: (a) behavioural response by scan sampling technique; (b) immune response at cellular level (skin test), by injection of phytoemoagglutinin (PHA) and at humoral level, injecting keyhole limper haemocyanin (KLH); furthermore, ACTH test was performed. The obtained results suggest that, compared to younger categories, heifers are less sensitive to stress induced by a high rearing density.] La prova è stata condotta su 40 manze di circa 19 mesi di età; a 20 di esse sono stati assegnati 2,3 indoor + 15 outdoor m quadrati/capo e alle altre 20 soltanto 2,3 indoor m quadrati/capo. Entro ciascun trattamento, sono stati adottati 2 livelli proteici della razione: alto (10 soggetti) e basso (10 soggetti). Per il monitoraggio dello stress si è proceduto alla valutazione: (a) della risposta comportamentale mediante la tecnica scan sampling e (b) della risposta immunitaria a livello cellulare (skin test), somministrando phytohemagglutinin (PHA), e a livello umorale, iniettando keyhole limpet haemocyanin (KLH); inoltre, è stato effettuato il test dell´ACTH. I risultati ottenuti indicherebbero che, rispetto alle categorie più giovani, le manze sono meno sensibili alla condizione stressante indotta da un´elevata densità di allevamento